P473Safety and efficacy of direct oral anticoagulants compared to vitamin K antagonists in patients with atrial fibrillation undergoing percutaneous coronary interventions: A meta-analysis. (18th June 2020) - Agasthi, P; Lee, J Z; Pujari, S H; Tseng, A S; Shipman, J; Almader-Douglas, D; Ashraf, H; Mookadam, F; Fortuin, F D; Beohar, N; Arsanjani, R; Mulpuru, S K
Abstract: Background: Coronary artery disease (CAD) and atrial fibrillation (AF) are commonly associated. Co-treatment with multiple anti-thrombotic agents can increase the risk of bleeding. Purpose: We sought to evaluate patient-centered outcomes in patients with AF on double therapy with direct oral anticoagulants (DOACs) compared to patients with standard triple therapy, [a vitamin K antagonist (VKA) plus dual antiplatelet therapy]. Methods: We performed an extensive systematic review of the literature and meta-analysis of randomized controlled trials reporting outcomes of patients receiving double therapy with DOACs compared to triple therapy with VKAs in patients with AF undergoing percutaneous coronary intervention (PCI). Patient-centered outcomes were the International Society of Thrombosis and Hemostasis (ISTH) major or clinically relevant non-major bleeding (CRNB), all-cause mortality, major adverse cardiovascular events (MACE), myocardial infarction, stent thrombosis, and stroke. Results: Four randomized controlled trials (9602 patients) met our inclusion criteria. Compared to VKAs, DOACs were associated with significantly lower ISTH major bleeding/ CRNB (RR - 0.75, 95% CI: 0.67-0.82, p < 0.00001, I2 = 11%). There were no statistically significant differences in the efficacy outcomes, including myocardial infarction (RR- 0.99, 95% CI :0.79-1.25, p = 0.96, I2 = 0%), stent thrombosis (RR - 0.97, 95% CI: 0.6-1.55, p = 0.89, I2 = 0%), ischemic stroke (RR - 0.76, 95% CI: 0.5-1.15, p = 0.19, I2 = 0%), all-cause mortality (RR - 1.06, 95% CI: 0.85-1.31, p = 0.61, I2 = 0%) and MACE (RR - 1.06, 95% CI: 0.91-1.22, p = 0.97, I2 = 0%). Conclusion: Compared with triple therapy with VKAS, double therapy with DOACs is associated with a reduced risk of bleeding and is as effective in patients with AF undergoing PCI.